Thermoluminescence studies of ordinary chondrites in the Japanese Antarctic meteorite collection, IV: Asuka ordinary chondrites - Ninagawa, Kiyotaka; Mieda, Yasuyuki; Ueda, Hiroyuki; Imae, Naoya; Kojima, Hideyasu; Yanai, Keizo (National Institute of Polar Research, 2005)
P(論文) We measured TL properties of ninety Asuka (A) ordinary chondrites (LL: 16, L: 27, H: 47) from Japanese Antarctic meteorite collection. Most of the chondrites had TL sensitivities over 0.1, corresponding to petrologic subtype 3.5-3.9. Eight chondrites, A-881244 (L3), A-881607 (LL3), A-881328 (LL3), A-881408 (LL3), A-881397 (LL3), A-881522 (L3), A-881357 (LL3 or L3), and A-881199 (LL3) were revealed to be primitive ordinary chondrites under petrologic subtype 3.4, and therefore they are particularly significant in understanding the nature of primitive material in the solar system. Twenty-one chondrites with low TL sensitivities below 0.1 (Dhajala=1) had suffered remarkable shock and/or terrestrial weathering. Samples were mainly from three different dirt bands south of the Sr Rondane Mountains at D1, D2, and D3 sites. LT/HT distribution at D1 site suggested that chondrites at D1 site had shorter terrestrial ages than those at D2 and D3. A-880709, A-88710, A-88774, A-881324 which had extremely low LT/HT ratio under 0.1, and A-881484 and A-881546 which might be heated over 400°C were presumed to have small perihelia. We found 26 TL potential paired fragments, and 9 groups. A group of H3 at D1 site comprises a chain of paired fragments. A H3 chondrite might shower near the Asuka. departmental bulletin paper